KONSEP PENDIDIKAN KARAKTER PERSPEKTIF UMAR BARADJA DAN RELEVANSINYA DENGAN PENDIDIKAN NASIONAL - Muhammad Hasyim (CENDEKIA: Jurnal Studi Keislaman, 2015)
Umar Baradja’s education concept of character has been adjusted to the concepts and objectives of national education. The result of the research on Umar Baradja’s thinking of character education is originated from Umar Baradja’s concept of interactions among social being. It was designed to prepare the next generation to be a virtuous, good, and noble human being. It was designed to able to be applied in all ages as well, from early childhood up to old age. Morals can be generated by the exercise and the struggle in the beginning, until it became a character. For example a person who wants to have a beautiful writing, the first time he had to force himself to imitate the beautiful writings, until the writing is his character. It is not strange to the man who was given by God a reason and understanding. Even, Similarly, it is not strange on wild animals, because their instinct can be transformed to be benign by exercises. It is evident that the dog can be taught to hunt and guard. Umar Baradja is a muslim leader from Surabaya. He was famous in his day until today. Alhamdulillah, his works still exist, taught in almost all pondok pesantrens (boarding schools). He offered education concept of character and by instilling and familiarizing a good behavior to Allah, His Prophet, and fellow human beings interact, and uphold the values ​​of brotherhood. Thus character education according to Umar Baradja’s as defined in this study are the concepts or moral message and the process of instilling to humans from themselves, to others, to God and even to inanimate objects. According to Umar Baradja people must try to get good behavior although at the beginning it seemed difficult that they will get used to the good behavior with constantly implementation.